The efficacy of silastic rtv 382 as a root canal filling material clearing technique - Lee, Jocelyn; Valmonte, Brenda; Jimena, Edna (Adviser)+.
Our purpose is to study in vitro silastic RTV 382 as a root canal filling material for its flow characteristic, ability to conform to prepared canal and to apical preparation with the use of the clearing techniques. A total of 36 transparent teeth were examined under the Baucsh and Lomb dissecting microscope Silastic RTV 382 mixed with 360 medical grade fluid and a dye was injected into the prepared root canal. The clearing technique used to make the teeth transparent rendered the filling material visible for examination and the injected silastic filling material exhibited good flow characteristic but showed the lack of density as a root canal filling material. Based on these findings, it could be said that silastic could be used as a root canal filling material and to shorten the obturation time. However, it did present difficulty in its manipulation and radiopacitywas no more than that of the tooth. Such that the manipulation of this material should be mastered and a pacifier like barium sulphate should be added in this material.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.